Attenuation Characteristics of Blast-Induced Stress Waves from Field Measurements - Kai Rong; Zong-Xian Zhang; José A. Sanchidrián; Adeyemi Aladejare; Li-Yuan Chi; Pablo Segarra (Geotechnical and Geological Engineering, 2026)
The attenuation characteristics of stress waves were studied based on 16 small-scale single-row blast tests at Otanmäki mine. In each test, the primary joint orientation was documented, two monitoring points were positioned at different distances from the blastholes, and the particle velocities in three orthogonal directions were measured. Seismic curves for the three components are shown under both short- and long-delay blasts. The attenuation laws of peak particle velocity ( PPV ) vector resultant derived from the radial, transverse and vertical particle velocity time histories, as well as seismic energy, with respect to scaled distance under three different primary joint orientations were analysed. The results show that the attenuation of stress waves is smallest when joints dipping into the face and greatest when joints dipping out of the face, and this difference may be attributed to the variations in the energy transmission efficiency of stress waves across joints under different incident angles. The geometric attenuation law of stress waves was analysed, which varies with the relationship between measuring distance and wavelength. According to this law, a modified charge scaling law was proposed in the form of a piecewise function. The validation results indicate that this law has practical applicability to a certain extent.